Analysis of the influence of zinc stannates and keratin powder on the flammability properties of epoxy material - Półka, M.; Kukfisz, B.; Kulik, A. (Polimery, 2021)
This paper analyses the impact of selected flame retardant additives on the combustibility and fire properties of epoxy materials based on Epidian 5 (Ep 5). The prepared epoxy resin was modified to increase its fire resistance using zinc hydroxystannate(IV) (ZHS), zinc stannate(IV) (ZS) and waste material – keratin powder (KR). The cone calorimeter was used to determine the heat and smoke release rates of burning composite samples using heat flux density of 30 and 50 kW/m2. Also, thermogravimetric analysis of the flame retardant modified and non-modified epoxy materials was performed. It was found that fire retardant additives ZS and ZHS added to the epoxy resin Ep 5 effectively decreased the heat release rate of the burning samples of cured resin and could significantly limit the spread of fire.